Territorialisation à distance par caméra vidéo : Perception de la vidéosurveillance au quartier des Pâquis à Genève - F. Klauser; R. Kaenzig (Geographica Helvetica, 2017)
Drawing upon two public opinion surveys conducted in Geneva in 2015 and 2016, the paper explores how video surveillance was lived and perceived by the residents of the monitored Pâquis area, as well as by the population at large. This study shows that the delegation of control to systems and individuals that are both spatially and socially detached from the monitored areas also results in a kind of `mental distance' that characterizes the relation between the monitored individuals and the system: People quickly forget about the cameras and withdraw from any conscious attempt to imagine what might be going on behind their back. The system thus gradually loses its relevance in people's everyday life. This, in turn, limits the symbolic power of the cameras to enduringly revitalize, and thus to properly re-territorialize, the monitored areas.